INDUSTRIAL IMPLEMENTATION AS A RESEARCH WORK KEYNOTE OF THE ELECTRICAL DRIVES AND ELECTRICAL MACHINES DEPARTMENT - Jarzyna, Wojciech; Zieliński, Dariusz (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2014)
The paper presents current offer of the implementation research at Electrical Drives and Electrical Machines Department at Lublin University of Technology. The offer was presented on the background of the historic activity of Department led by former managers. The practical nature of the research was emphasized. Implementation directions including, i.e. drives and passenger lifts control, electromechanical systems powered by renewable solar and wind power cooperation to the grid were distinguished. The active participation of the department employees and PhD students in adapting the educational offer to the market needs, as well as postgraduate staff training were also noticed.